Obscurity of Camp Life: Is the Language of Camp 'Passivity to Write'? - Datta, Joydip (Sanglap : journal of literary and cultural inquiry, 2019)
(Bose; Sanyal) This paper aims to think the question of caste spatially where Partition is seen as the ruins of past experiences. [...]camps considered here are not only thought of as concentration of the refugees, but it also indicates the phenomenon of caste in Bengal and explores the meaning of camp considering this reality. Description directed towards camp or asylum as the space of protection of the refugees, introduces a corollary obligation for the state to help them and it does so according to the institutionalized principle of the League of Nations^On the other side, the facts of this spatial consideration have been counted according to the law of physical structure of the camp and policy for the rights of asylum or camp inmates. The existence of camp was very purposive and it was the immediate assistance given to the people whose way of life was disrupted. [...]in-itself camp belonged to such a destiny of the being, which is actually the affirmation of the abandonment of home and makes 'itself of refugee' known by the essence of the spatial arrangement. To investigate the truth of the 'being' of camp in a post-metaphysical way is to understand the reality. [...]in-itself camp is a kind of temporal arrangement for the refugee families.